Seeking justice for the mass execution in Rawagede/ Probing the concept of 'entangled history' in a postcolonial setting. Issue 1 (2nd January 2020) - Immler, Nicole L.; Scagliola, Stef
ABSTRACT: In the Netherlands, the nation's imperial past is under new scrutiny since a landmark decision of the Civil Court in The Hague in 2011 held the Dutch state responsible for a mass execution perpetrated in 1947, during the Indonesian war of independence (1945–1949). This paper explores some of the historiographical implications of this triumph of law, arguing that it has had the unintended effect of reinforcing the representation of the conflict along 'national' frames at the expense of the more 'entangled' experiences of the actors involved. The authors hereby respond to Remco Raben's call to write 'trans-colonial' history in order to overcome the dominance of national frames in Dutch postcolonial historiography. By bringing the pre-history and the afterlife of the court case to the fore, the authors show how 'entangled' the (hi)stories of veterans, victims, and activists are, and how alternative 'frames' than that of the nation state, could contribute to develop the much awaited postcolonial historiography.